A receiver-based forwarding scheme to minimize multipath formation in VANET - Husain, K. (Springer Verlag, 2017)
Receiver-based data forwarding schemes are well suited for vehicular environment due to their ability of making routing decision on the fly. However, existing receiver-based schemes still face the challenges of unwanted multiple paths formation especially when contending nodes are out of transmission range of each other. In this paper, we propose an approach of the receiver-based forwarding scheme where receiving nodes decide whether to participate in contention for forwarding right based on signal-to-interference-plus-noise ratio (SINR) and forwarding zone. Upon qualifying to contend for forwarding right, the contending nodes set their waiting time based on geographical progress toward destination. We present the proposed scheme and then highlight some possible issues that require further investigation. The proposed scheme tends to minimize unnecessary formation of multiple paths toward the destination while also favors the selection of a forwarding node closer to destination. © Springer Nature Singapore Pte Ltd. 2017.